Aging-related geniohyoid muscle atrophy is related to aspiration status in healthy older adults - Feng, Xin; Todd, Tee; Lintzenich, Catherine R; Ding, Jingzhong; Carr, Jeffery J; Ge, Yaorong; Browne, James D; Kritchevsky, Stephen B; Butler, Susan G (The journals of gerontology. Series A, Biological sciences and medical sciences, 2013)
Age-related muscle weakness due to atrophy and fatty infiltration in orofacial muscles may be related to swallowing deficits in older adults. An important component of safe swallowing is the geniohyoid (GH) muscle, which helps elevate and stabilize the hyoid bone, thus protecting the airway. This study aimed to explore whether aging and aspiration in older adults were related to GH muscle atrophy and fatty infiltration. Eighty computed tomography scans of the head and neck from 40 healthy older (average age 78 years) and 40 younger adults (average age 32 years) were analyzed. Twenty aspirators and 20 nonaspirators from the 40 older adults had been identified previously. Two-dimensional views in the sagittal and coronal planes were used to measure the GH cross-sectional area and fatty infiltration. GH cross-sectional area was larger in men than in women (p < .05). Decreased cross-sectional area was associated with aging (p < .05), and cross-sectional area was significantly smaller in aspirators compared with nonaspirators, but only among the older men (p < .01). Increasing fatty infiltration was associated with aging in the middle (p < .05) and posterior (p < .01) portions of the GH muscle. There was no significant difference in fatty infiltration of the GH muscle among aspirators and nonaspirators. GH muscle atrophy was associated with aging and aspiration. Fatty infiltration in the GH muscle was increased with aging but not related to aspiration status. These findings suggest that GH muscle atrophy may be a component of decreased swallowing safety and aspiration in older adults and warrants further investigation.